HASIL KALI SILANG ω- SUBSEMIRING FUZZY - Saman Abdurrahman; Thresye Thresye; Alya Hanifah Arif; Jumiati Jumiati; Tiara Roihatul Jannah (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2023)
Fuzzy semirings are one of the results of a combination of semirings and fuzzy sets. Semiring is one of the extensions of the ring. The cross product of two or more semirings gives a semiring. We are motivated to conduct cross-product research on fuzzy semiring based on the condition of cross-product semiring. This paper introduces the direct product of two (more) fuzzy subsemirings. In addition, we investigate the relationship between the cross product of two (more) fuzzy subsemirings and the cross product of two (more) level subsets that are subsemiring